Análise crítica das analogias do livro didático público de química do Estado do Paraná - Bernardino, Mychelle Amorim Defenti (2010)
The analogies in education, particularly in the sciences of nature, have the role to help the student to understand unknown concepts and phenomena, through comparisons of similarity attributes with other ones known. In this context, analogies can be considered a resource with great didactic potential in teaching and learning process. Considering that schoolbooks are the main material for many teachers, the purpose of this research is to identify and study the analogies of the public Chemistry schoolbook from Paraná State. This work is based on Gaston Bachelard's theoretical assumptions, specifically those which refer to the epistemological obstacles. To identify and categorize analogies distributed in fifteen chapters of the schoolbook, we based on Mol (1999) to understand the definition of analogy. The adopted criteria by Monteiro and Justi (2000) and Francisco Junior (2009) guided the data compilation. As results, we found twenty five analogies, covering the different chemistry topics of the book. It is necessary to emphasize that the topics that presented more analogies were the chemical bonds and the atomic structure. According to "level of enrichment" criterion, twenty-two of the analogies found are simple, that is, they share a single attribute. Moreover, the authors of the chapters of this book do not bring explanations for the understanding of these analogies nor warn about the possible limitations concerning their use. Among the main results, we can also infer that the most of the analogies found in the analyzed material can generate animist and realistic epistemological obstacles.